Are advertisements shaping our consciousness? An Analysis of selected chinese new year print and tv advertisements - Ng, Chee Huat (2008)
Social scientists have long believed that cultural values differ widely, particularly around such socially embedded issues as status, gender, family, ethics, and mores. Advertising helps to affect a “transfer of values” by establishing a nexus between what a culture views as desirable states of being and particular products. This research is a study on print advertisements during the 2007 Chinese New Year session that appeared in the main English daily, The Star. To what extend does Chinese New Year messages affect consumers‟ consciousness on cultural values? Semiotic analysis and personal interviews were used to answer these research questions. Consumers are aware of the commercial driven-purpose of these advertisements. They appeared to know the intention of the advertisers of “playing with their consciousness” and had thus put up their defenses.